Islands under threat : heterotopia and the disintegration of the ideal in Joseph Conrad's Heart of darkness, Antjie Krog's Country of my skull and Irvan Welsh's Marabou stork nightmares - Pieterse, Annel (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2005.